New Solid State Sensor for Gas Detection Based on Carbon Nano-Tube Fortified by Fe2O3-ZnO - Kazemzadeh, A. (Asian Journal of Chemistry, 2012)
In this paper multi-wall carbon nano-tubes were prepared by using chemical-thermal vapour deposition method and utilizing molybdenum and iron catalysts and silica alumina-base. Methane was passed over catalyst in optimum condition including passing speed equal to 4 L/min and pressure of 1.27 bar for 2-25 min and temperature of furnace was equal to 980 ºC. Diameter and specific area of nano-tubes were 10-70 nm and 400-560 m2/g respectively. Various quantities of Fe2O3-ZnO and 0.1 % palladium were inserted in carbon used for prepared nano-tubes by utilizing vacuum evaporation which its optimum quantity was [2.50 % (1/1 w/w) Fe2O3-ZnO] and 0.1 % palladium in order to enhance sensitivity of carbon nano-tubes relative to NH3 to make sensors appropriate for low temperatures. For investigation instruments and determining physical properties, XRD, SEM and TEM equipments have been applied and prepared. NH3 sensor is simple, low cost and ready to use in various environment.